(untitled) (SCHOOLAR: Social and Literature Study in Education, 2022)
This research aims to help the students and teachers in learning English material especially for listening and speaking skills. The students can utilize information technology in learning process based upon their needs. The research is about instructional media for listening and speaking skill based power point hyperlink as learning media. The subject of this research are the tenth grade students in MA Unggulan Wahab Hasbullah Tambakberas Jombang. This research design is research and development. This research adapted ADDIE model which consists of five stages such as analysis, design, development, implementation, and evaluation. The the researchers used questionnaire and interview as data collection of the technique to get respons from the product. PIVI Apps was validated by media expert and material expert before tried out to the students. Based on the result, the score of this product by media expert is 3,71 score aand score by material expert is 4,33 , the score categorized is â€œagree/relevantâ€. The the researchers concluded that the students were agreed in learning English using PIVI Apps as learning media. Keywords: Listening, Speaking, PIVI Apps, Senior High School